Effect of age and sex on the association between lipid profile and obesity among telecomunication workers in Palembang (Faculty of Medicine Universitas Indonesia, 2007)
The study objective is to examine the effects of age and sex on the association between various obesity parameters and lipid profile. The measurements of whole body obesity (body fat, body fat % and BMI), abdominal obesity (waist to hip ratio, waist to thigh ratio and waist circumference) and lipid profile (HDL, LDL, VLDL, total cholesterol and triglyceride) were performed on 112 telecom workers in Palembang (84 men and 28 women, age 25, 35, 45, and 55 years). All lipid parameters results depend on sex and age of subjects. The association between obesity assessments and HDL or LDL was independent of sex and age of subjects, whereas the association between obesity assessments and total cholesterol, VLDL and triglyceride is dependent on sex and age of subjects. Abdominal obesity has greater effect on VLDL and triglyceride levels than on other lipid parameters. Whole body obesity has equal effects on all lipid parameters. When comparing results of male and female subjects, obesity measurements and lipid profile association is stronger in male subjects of almost all age groups. The exception is a stronger association between abdominal obesity and VLDL or triglyceride levels in 45 years old female subjects. Obesity measurements and VLDL or triglyceride level association is independent of age, whereas obesity and total cholesterol association is stronger in younger subjects. (Med J Indones 2007; 16:251-6)